THE MAKING OF LEARNING VIDEO â€œLEARNING ENGLISH ADJECTIVE COMPARISON WITH HARRY POTTER MOVIESâ€ - Eric Sander; Rionaldi Rionaldi (INOVISH JOURNAL, 2020)
The purpose of the study is to make learning English adjective comparison with Harry Potter movie. The method of this study is descriptive research. There were four processes in making the learning video. The first was collecting materials and planning the video, the second was writing the video script, the third was editing the video and the last was making the subtitle. The result of the study was an 18 minute Video about English adjective comparison with Harry Potter movies. It consists of introduction, the nature of adjective comparison, kinds of adjective comparison and the examples taken from movie scenes for. This video is a good alternative for learner to learn about adjective comparison from movie.